PENGGUNAAN METODE BELAJAR BERBASIS PROBLEM – BASED LEARNING UNTUK MENAIKAN KETUNTASAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PROGRAM LINEAR DI KELAS XII IPA-1 SEMESTER GANJIL SMA NEGERI 1 PINANGSORI TAHUN PELAJARAN 2017/2018 - Merintan D Hutapea (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
There is a trend in the world of adult education is to get back on the idea that the child will learn better if the environment is created for real. Learning will be more meaningful if the child is experiencing its own what is studied, then approach based on the problem( Problem Based Learning ) as an option to turn the classroom so that students are taught with real, thus achieving results optimal learning.This research was conducted in SMA Negeri 1Pinangsori, held on 25 September to 25 November 2017. The research plan used is the class Act (PTK),and the criteria used include research qualitative research. Because the data source directly and using research as a gatherer of primary data. Based on the results of this research show that learning with the method of Problem Based Learning on the subject of Linear Programs can improve ketuntasan learning that is the average value of ketuntasan studied by 86.22 75.23%. The expectations of researchers, hopefully with the experience of researchers can be beneficial for a peers plunge in the world of education. Keywords: Motivation, Learning Outcomes learning, Berbasis Problem Based Learning, Linear Program.